R&D tax credits, innovative activity and the targeting approach - Gjymshana, Erik; Roggeman, Annelies; Verleyen, Isabelle (Economics and Business Review, 2025)
The aim of this study is to investigate if the French R&D tax credit targeted at small and medium-sized enterprises (SMEs) has a positive impact on innovative activity. The French institutional setting provides a unique research setting as the R&D tax credit targeted at SMEs only applies to expenditures incurred during the development phase of R&D projects instead of all eligible R&D expenditures. In order to explore the effectiveness of the French R&D tax credit, a regression discontinuity design (RDD) is applied by comparing targeted SMEs with larger firms not subject to the tax credit over the period 2014-2018. In general, we find that the French R&D tax credit has a positive impact on innovative activity. Moreover, SMEs react more strongly to this incentive in their growth stage. The findings suggest, however, that this effectiveness in increasing SMEs’ innovation does not persist over time.